SURVEI KEBUGARAN JASMANI MAHASISWA PRODI PENJAS SEMESTER III FKIP UNIVERSITAS MAJALENGKA TAHUN 2019/2020 - Mohamad Sadikin; Indra Prabowo; Didik Subhakti Prawira Raharja (JOURNAL RESPECS, 2021)
ABSTRACT. The background of this research is the lack of movement or sports activities among students. The purpose of this study was to determine how much the level of physical fitness of the third semester students of the Physical Education Study Program FKIP Majalengka University 2019/2020. The method used in this research is descriptive method. The population in this study were 63 students from semester 3 A-C Physical Education Study Program, Majalengka University. The research sample was determined by incidental sampling. The research sample was 50 students. The instrument in this study was the bleep-test. To analyze the data obtained using relative frequency distribution analysis. Based on the results of the study, it shows that there is a difference between students who often do physical activity (sports) and those who rarely do physical activity (sports), the level of physical fitness is better for students who often exercise. Thus, physical activity greatly affects the physical fitness of the students themselves. Therefore, to get good fitness, students are required to be more diligent in doing physical activity (sports), so that they can move smoothly and not get sick easily.Key word: Physical fitness; College studentABSTRAK. Latar belakang penetitian ini adalah kurangnya aktivitas gerak atau olahraga dikalangan mahasiswa. Tujuan dari penelitian ini adalah untuk mengetahui seberapa besar tingkat kebugaran jasmani mahasiswa semester III prodi penjas FKIP Universitas Majalengka 2019/2020. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Populasi dalam penelitian ini adalah 63 mahasiswa dari semester 3 A - C Prodi Pendidikan Jasmani Universitas Majalengka. Sampel penelitian ini ditentukan dengan Sampling insidental. Sampel penelitian sebanyak 50 mahasiswa. Instrumen dalam penelitian ini adalah bleep-test. Untuk menganalisis data yang diperoleh menggunakan analisis distribusi frekuensi relatif. Berdasarkan pada hasil penelitian menunjukkan bahwa adanya perbedaan antara mahasiswa yang sering melakukan aktivitas fisik (olahraga) dengan yang jarang melakukan aktivitas fisik (olahraga), level kebugaran jasmaninya pun lebih baik mahasiswa yang sering berolahraga. Dengan demikian bahwa aktivitas fisik sangat mempengaruhi kebugaran jasmani mahasiswa itu sendiri. Maka dari itu juga mendapatkan kebugaran yang baik mahasiswa dituntut untuk lebih rajin melakukan aktivitas fisik (olahraga), agar bisa beraktivitas dengan lancar dan tidak mudah sakit.Kata Kunci: Kebugaran Jasmani; Mahasiswa.